(untitled) - Aucamp, Armand

Development of a pre-selection index for cider apple (Malus x domestica Borkh.) genotypes by phenotyping a low-chill requiring red-fleshed breeding progeny (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2025.